2015
DOI: 10.2991/ict4s-env-15.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Motivational Affordances for Meaningful Gamified and Persuasive Technologies

Abstract: Sustainable human-computer interaction is investigating the role of persuasive and gamified technologies in encouraging people to engage in a more sustainable lifestyle. Motivation is a key requirement for behavior change, yet many persuasive systems do not sufficiently account for motivational aspects. In this paper we investigate under which circumstances components such as feedback and game elements (e.g., rewards) afford user motivation. The result is a taxonomy of design components that is grounded in wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 62 publications
1
40
0
22
Order By: Relevance
“…Nevertheless, from meta-analyses it is known that feedback does not always have a positive effect on performance [82] or the desired effect on self-efficacy [83]. According to van de Ridder et al [84] this is because of the different ways in which feedback can be provided, including the various possibilities of framing (positive-negative), level of detail, or the timing of feedback (instantly or in an accumulated (offline) form) [85]. Although de Ridder et al [84] have also demonstrated positive effects on performance and self-efficacy, self-efficacy itself seems to have a moderating effect and therefore influences the acceptance of feedback as well [86].…”
Section: Designing Gamification To Promote Sustainable Nutritional Bementioning
confidence: 99%
“…Nevertheless, from meta-analyses it is known that feedback does not always have a positive effect on performance [82] or the desired effect on self-efficacy [83]. According to van de Ridder et al [84] this is because of the different ways in which feedback can be provided, including the various possibilities of framing (positive-negative), level of detail, or the timing of feedback (instantly or in an accumulated (offline) form) [85]. Although de Ridder et al [84] have also demonstrated positive effects on performance and self-efficacy, self-efficacy itself seems to have a moderating effect and therefore influences the acceptance of feedback as well [86].…”
Section: Designing Gamification To Promote Sustainable Nutritional Bementioning
confidence: 99%
“…This focus aligns with the assessment that reflective and automatic motivation toward smoking cessation can be enhanced by interventions, such as education, persuasion, intensification, coercion, and modelling [20]. However, the actual content component of the app itself is flexible and has been designed to be easily updatable as new content is developed.…”
Section: Introductionmentioning
confidence: 91%
“…Within the cycle of design and development, the initial Game Mechanic and Elements design phase was informed by a taxonomy of motivational affordances for meaningful gamified and persuasive technologies (Figure 1) [20]. This taxonomy describes a set of design components that is grounded in well-established psychological theories on motivation [20].…”
Section: Introductionmentioning
confidence: 99%
“…This forced us to promote that users should interact with the app on a daily basis, instead of after every activity they completed. While this is acceptable for mere data collection, many user interactions rely on well-timed feedback, and are thus out of reach for such an application setup [15].…”
Section: Challengesmentioning
confidence: 99%
“…Participants are recruited on a voluntary basis and live in the Swiss cantons of Zurich and Ticino. We involve them in three mobility tracking periods: in a first one-month monitoring period (Spring 2016) we track their movements to identify baseline mobility patterns; in a second three-months period (Autumn 2016) we continue tracking movements and also use "gamification" [15] elements to challenge them to modify their mobility patterns; the final period (Spring 2017) is used to study long-term effects. Comparing the individual mobility patterns of the three periods allows us to assess the overall effectiveness of the GoEco!…”
Section: Mobility Monitoring For Sustainabilitymentioning
confidence: 99%